The Effect of Conceptual Factors on Small and Medium-Sized Enterprises Business Success in Malaysia - Husain, Nor Azmawati; Abd Rashid, Intan Maizura; Norhisham, Norshiba; Mohd Noor, Nor Hamiza; Kamarolzaman, Noraishah (Information Management and Business Review, 2023)
This study was purposely conducted to examine the influence of conceptual factors such as external environment (i.e. government support and information access) and managerial expertise (i.e. business planning and entrepreneurial skills) on SMEs business success in Malaysia. The main objectives are to examine which factors that influences most on SMEs’ business success. A survey was administered through a face-to-face approach to 115 individuals who run the SME business. We utilized SPSS version 20 software and analyzed the data using multiple regression analysis to test the hypothesis. Findings showed a significant relationship between all tested variables (government support, information access, business planning & entrepreneurial skills) and the dependent variable (business success of SME). Through multiple regression analysis, although all variables tested have a significant effect on SMEs’ success, however, a greater influence is shown by entrepreneurial skills on the probability of SMEs’ success. Findings are expected to contribute to improve the understanding of the obstacles or challenges that might be faced by SMEs. These findings also benefit policymakers and development partners to formulate policies related to improvement for SMEs. The useful information will help the SMEs continue to grow. At the same time, the government also can promote the development of competitive, innovative, and resilient SMEs through effective coordination and provision of business support that focuses on improving entrepreneurial skills. The research is useful for development partners in developing programs including searching for funds. Lastly, this study hopes to contribute to the body of knowledge concerning SMEs in Malaysia.